ZAKAT PRODUKTIF DALAM PEMBERDAYAAN EKONOMI MASYARAKAT MASA PASCA PANDEMI COVID 19 DI BAZNAS KABUPATEN CIREBON - Sri Anah (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2023)
Zakat is related to social and economic problems. In the social field, zakat can eliminate poverty by giving awareness to rich people or wealthy people of social responsibility, while in the economic field, zakat can prevent the accumulation of wealth in the hands of individuals. Drastic. The current condition of the country is unstable in various fields, namely the economy, education, health, religion, social and culture. This condition occurred due to the Covid-19 outbreak that hit various countries.This research method is carried out using qualitative research, a process of research and understanding based on a methodology that investigates a social phenomenon and human problems.The results of this study concluded that during the Covid19 pandemic carried out by BAZNAS Cirebon Regency, namely following the Covid-19 handling protocol while maintaining physical distancing, social distancing and always wearing a mask, the distribution approach was by coming directly to the mustahik place (push approach), coordinating with the Cirebon Regency BPBD and coordination with village officials who already have a Covid-19 task force. In empowering small trader businesses, economic empowerment programs are able to realize the welfare of the people. As for the form of small trader business capital loans in which the funds must be used for business.Â Keywords: Productive Zakat, Economic Empowerment, and BAZNAS Cirebon.